DATA PROCESSING SYSTEM IN VALUE RAPORT BALI VILLAGE SDN 03 PAGI - Marlian Masri; Eko Hadiyanto. SSi. MMSi Eko Hadiyanto. SSi. MMSi (Jurnal Sistem Informasi, 2002)
Number of information that is not regularly within the running system so that theprocessing value rapot look long and complicated. In the old system a lot of work todo it manually by teachers and elementary school homeroom Kampung Bali 03 Pagi,a constraint that is often encountered in the current system.If the proposed system has been running, the obstacles encountered in the runningsystem is expected to be overcome. Information provided to students and parents ofstudents Elementary School Kampung Bali 03 Morning becomes faster and moreaccurate because the data stored adanaya mediated storage into a file.In addition in this new system is expected to faculty related especially teachers andhomeroom teacher had no difficulty in obtaining the information needed, includingmaking the value of report cards, and report the value of report cards.